Effect of indoor design temperature on the heating and cooling transmission loads - Ozel, Meral (Elsevier, 2016)
In this study, the effect of indoor design temperature on cooling and heating transmission loads through walls is investigated numerically over the whole year. The investigation is carried out for different wall orientations in the climatic conditions of Elazig, Turkey. For this purpose, as indoor design temperature is increasing from 18 to 26 degrees C, the transmission loads are calculated using an implicit finite difference method under steady periodic conditions. It is noted that south wall provides minimum heating load while north wall provides minimum cooling load. It is seen that as indoor design temperature increases, the heating transmission loads increase while the cooling transmission loads decrease. Results show that the cooling transmission load decreasesl6-27% with every 2 degrees C rise of indoor design temperature while the heating transmission load increases 18-30% for all wall orientations with every 2 degrees C rise of indoor design temperature. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Indoor design temperature; Cooling and heating transmission loads; Wall orientations